Insiden dan Etiologi Kelumpuhan Saraf III, IV dan VI yang disertai Diplopia Binokuler di RSUD DR. Wahidin Sudirohusodo - Dhany, Rini Kusumawar; Tanjung, Yunita; Jennel, Farren (Universitas Wijaya Kusuma Surabaya, 2019)
The purpose of this study is to determine the incidence and etiology of III, IV and VI nerve paralysis with binocular diplopia in RSUD dr. Wahidin Sudiro Husodo General Hospital Mojokerto. Method of this study was descriptive study using secondary medical record data. Incidence rates are adjusted for age and sex distribution of the population. The mean age of onset was 45.6 years, seven male subjects (58.3%) and five female subjects (41.7%). We identified 12 cases of acquired III, IV and VI nerve palsy over a 4-year period. The most common cause of binocular diplopia was sixth nerve palsy (33.3%), 3 patients experienced partial third nerve palsy (25%), one patient with third nerve palsy with pupil sparing (8.3%). Most common etiology was microvascular (58,3%), neoplasms (16.7%), aneurysms (8.3%) trauma (8.3%), and post meningioma neurosurgery (8.3%). Six patients (50%) with microvascular third nerve palsy had diabetes mellitus, while 1 patient (8.3%) had grade 2 hypertension. The most common cause of binocular diplopia was VI nerve palsy. Risk factors such as hypertension and diabetes mellitus which have a significant effect on diplopia. Patients with N. III, IV and VI palsy need to be done early MRI examination so that complications and progression can be prevented.